An assessment of ancient DNA preservation in Holocene–Pleistocene fossil bone excavated from the world heritage Naracoorte Caves, South Australia. (13th January 2016) - Grealy, Alicia; Macken, Amy; Allentoft, Morten E.; Rawlence, Nicolas J.; Reed, Elizabeth; Bunce, Michael
ABSTRACT: Although there is a long history of research into the fossil deposits of the Naracoorte Caves (South Australia), ancient DNA (aDNA) has not been integrated into any palaeontological study from this World Heritage site. Here, we provide the first evidence of aDNA preservation in Holocene‐ and Pleistocene‐aged fossil bone from a deposit inside Robertson Cave. Using a combination of metabarcoding and shotgun next‐generation sequencing approaches, we demonstrate that aDNA from diverse taxa can be retrieved from bulk bone as old as 18 600 cal a BP. However, the DNA is highly degraded and contains a lower relative proportion of endogenous sequences in bone older than 8400 cal a BP. Furthermore, modelling of DNA degradation suggests that the decay rate is rapid, and predicts a very low probability of obtaining informative aDNA sequences from extinct megafaunal bones from Naracoorte (ca. 50 000 cal a BP). We also provide new information regarding the past faunal biodiversity of Robertson Cave, including families that have not been formerly described in the fossil record from here before. Collectively, these data demonstrate the potential for future aDNA studies to be conducted on material from Naracoorte, which will aid in the understanding of faunal turnover in southern Australia.